2010
DOI: 10.1259/bjr/14421796
|View full text |Cite
|
Sign up to set email alerts
|

Neurolinguistic programming used to reduce the need for anaesthesia in claustrophobic patients undergoing MRI

Abstract: ABSTRACT. The purpose of this study was to assess the success of neurolinguistic programming in reducing the need for general anaesthesia in claustrophobic patients who require MRI and to consider the financial implications for health providers. This was a prospective study performed in 2006 and 2007 at a teaching hospital in England and comprised 50 adults who had unsuccessful MR examinations because of claustrophobia. The main outcome measures were the ability to tolerate a successful MR examination after ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 12 publications
1
33
0
2
Order By: Relevance
“…[24][25][26][27][28] These were conducted in the US, 3 Denmark, 2 UK, 2 Croatia, Brazil, and New Zealand. Targeted health conditions include various anxiety disorders, 6 weight maintenance, morning sickness, substance misuse, and claustrophobia during MRI.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…[24][25][26][27][28] These were conducted in the US, 3 Denmark, 2 UK, 2 Croatia, Brazil, and New Zealand. Targeted health conditions include various anxiety disorders, 6 weight maintenance, morning sickness, substance misuse, and claustrophobia during MRI.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Delivery of NLP interventions ranged from three studies using a single 1-2 hour session 19,25,28 to the remainder offering 4-20 1-2 hour sessions. Duration of intervention was reported by six studies ranging from 4 weeks, 23 21 days residential, 26 …”
Section: Interventionsmentioning
confidence: 99%
See 2 more Smart Citations
“…After a review of studies in different fields, the following was observed: In the study of Sahebalzamani (25), it was concluded that programs on NLP should be conducted with students because NLP strategies contributed to the development of general health and its various dimensions. In the study of Bigley et al (26) conducted with patients with claustrophobia, anxiety scores of the patients who participated in the NLP sessions decreased significantly. Therefore, it can be said that NLP is not only effective in studies in the field of health but also an effective teaching strategy for in-service trainings.…”
Section: Discussionmentioning
confidence: 97%